Detection of Shiga toxin-producing Escherichia coli by sandwich enzyme-linked immunosorbent assay using chicken egg yolk IgY antibodies - Parma, Y. R. (2012)
Fil: Parma, Y. R. Instituto Nacional de Tecnología Agropecuaria. Centro Nacional de Investigaciones Agropecuarias. Instituto de Patobiología; Argentina.